Implementation of Blockchain Technology in UKTS Library: Challenges, Obstacles and Opportunities - Ekowati, Maria Atik Sunarti; Darsini , Darsini (CV. Science Tech Group, 2024)
Blockchain is a technology based on cryptography which uses the principle of distributed ledgers (distributed ledgers) distribution) provides a variety of advantages, especially in security matters. Use of distributed ledgers as the basis of blockchain technology turns out to be very similar to that concept is very familiar among libraries, namely LOCKSS (Lots of Copies Keep Stuff Save). This is the meeting point between blockchain technology and libraries. Starting from here, possibilities open up for libraries to implement blockchain technology. Various potential applications of blockchain technology for libraries include: procurement and maintenance of library materials, innovation in circulation services, cataloging, guaranteed protection of personal data and library membership cards, e-book publishing, support for scientific publications and digital rights management, management special collections, research support, financial literacy and UKTS library analysis. However, on the other hand, there are also challenges and obstacles that accompany efforts to implement blockchain technology in UKTS libraries, including: limited knowledge of blockchain technology, challenges in being able to choose the right blockchain, the large costs that must be incurred by libraries starting from implementation costs, maintenance costs to the costs of developing the blockchain system itself, and the last and quite sensitive issue is that there are still some people in scientific circles who think that the issue of personal data security in the blockchain system is not completely safe.